Perencanaan Tata Letak Gudang Dengan Metode System Layout Di CV. Eka Jaya Sakti Plant Rafia - Aditya Solichin; Febrina Agusti; Brillian Nur Diansari (Politeknik Kampar, 2023)
Facility layout design is very important in supporting production activities, this arrangement is supported in one area in the warehouse. Warehouse arrangement is necessary for the smooth flow of materials that require efficient arrangement and transfer of materials to reduce the frequency of backtracking. The purpose of this research is to minimize the material transfer distancehandling. CV. Eka Jaya Sakti is a company engaged in processing plastic into raffia products. The problems that exist in this company are the placement of raw materials and product results that are less organized. The method used in this research isSystematic Layout Planningthe analysis was carried out by comparing the total material handling initial displacement with the proposal. Materialhandlingin the initial layout is . the results of the proposed layout research with material spacinghandlingthe first proposal is 4,763.22 meters and the second is 3,678.6 meters. Based on these results, the proposed layout is chosen the second layout with the minimum displacement distance value.